Political Education in Times of Populism Towards a Radical Democratic Education - Sant, Edda.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
"In professional and academic contexts nothing is more important than helping people to understand and engage with democratic society. Sant has written an excellent book which helps greatly towards that end. She has developed incisive new arguments about the nature of contemporary politics and education. Using the most recent as well as classic literature, she explores key ideas and issues. Through wide ranging discussions and by referring to her own valuable empirical work she characterizes and creates thoughtful insights and innovative pedagogical approaches. This book achieves the very difficult task of illuminating complex ideas at the same time as helping to determine practical ways to achieve social justice through education. Political education has been neglected for too long. This book is a bold new step in its achievement." $1 (BIan Davies, Emeritus Professor, University of York, UK This book examines political education in times of democratic crisis, polarisation and uncertainty. Using populism as a diagnostic tool, the book scrutinises current democratic practices and considers alternatives for future social studies and citizenship education. The author examines contemporary events including Brexit, the Catalan referendum for independence and protests in Chile to ask how democratic educators can respond to times of crisis. Centered on themes of knowledge and ideology, the book draws together political philosophy and educational research to map out, critically analyse and offer alternatives to dominant debates on political education. It will be of interest and value to scholars examining the relationship between democracy and educational theory and practice. Edda Sant is Senior Lecturer at Manchester Metropolitan University, UK. A former social studies teacher, her research interests lie in citizenship, political and democratic education. She has published widely in this field, and in 2016 her co-authored article was recognized with a Children$1 (Bs Identity & Citizenship European Association Award.s
Introduction -- Chapter 1. Populism as a democratic threat -- Chapter 2. Radical democratic education -- Chapter 3. Expected responses from political education -- Chapter 4. Populism as a possibility -- Chapter 5. Alternative understandings of political education -- Chapter 6. Towards a different radical democratic education -- Chapter 7. The promotion of British Values in England (UK) -- Chapter 8. The 300th Jubilee of the national myth in Catalonia (Spain) -- Chapter 9. Limitations of this project -- Chapter 10. Concluding remarks: (3z(Bmy preference will always be democracy(3y(B, and yours?s
Keywords: Education and state; Educational sociology; Cultural policy; Political science$1 (BPhilosophy.s; Political sociology; Educational Policy and Politics; Sociology of Education; Cultural Policy and Politics; Political Philosophy; Political Sociology